Understanding the Knowledge and Practices of Patent Medicine Vendors towards Tuberculosis Control in a Semi-Urban Area of South-South, Nigeria - IN, Ojule; CM, Nwaike; BE, Kingian (International Journal of Innovative Research in Medical Science, 2020)
Background: Tuberculosis (TB) is a significant health and economic burden in our environment and consistently ranks amongst the most common disease that affects individuals whose immunity has been compromised. It is also one of the major infectious diseases that affect those living with HIV and AIDS. Patent Medicine Vendors (PMVs) are ubiquitous in our Communities and are highly patronized by the populace. This is because they are at close proximity, affordable and accessible to many underprivileged and underserved people in Low and middle income countries. Inadequate knowledge and practice among PMVs will increase morbidity, mortality and promote spread of TB and emergence of Multi-drug resistant strains of TB. The study therefore aimed to understand the knowledge and practices of PMVs towards TB control to enable appropriate intervention. Method: The study was of a descriptive cross-sectional design. Semi-structured self-administered questionnaires in English were administered to forty ‘in-charge’ Patent medicine vendors to obtain quantitative data on their socio-demographics, their knowledge and their practices towards clients who present with chronic cough or tuberculosis. Results: From our study, more than half (65.0%) of the respondents identified prolonged cough -lasting more than 2 weeks and bloody cough (75.0%) as symptoms of TB. Only 27.5% of the PMVs have heard of DOTS (Directly Observed Treatment Short-course). Only 20.0% of the PMVs were aware that TB treatment required a minimum of 4 different drugs while 60.0% of them knew that drug treatment of TB should last for a minimum of 6 months. The majority (80.0%) of the PMVs correctly answered that TB drugs in government hospitals are free. When asked the most important tests to request for a client with chronic cough, all (100%) the PMVs mentioned sputum test and X-ray. The result shows that most of the respondents had good practice on the management of tuberculosis because they tended to refer clients with chronic cough or confirmed cases of TB to the government hospital. In our study, level of education of the PMVs was significantly associated with good practice of TB management, p=0.005. Conclusion: From our study, we understood that the level of knowledge and practices of TB management among PMVs in Alakahia Community is fairly adequate as we assessed them based on knowledge appropriate for them. A lot more still need to be done in area of training and retraining of PMVs on knowledge and practices, as well as educating the public on proper health-seeking behavior.